Estudio para el desarrollo agropecuario de la cuenca del río Cañas, Nicoya, Provincia de Guanacaste, Costa Rica - Aguilar León, Luis A. (IICA, Turrialba (Costa Rica), 2014)
Tesis (Mag.Sc.) - IICA, Turrialba (Costa Rica), 1966